Penerapan Soft System Methodology dalam Ekstraksi Pengetahuan Tentang Akreditasi Universitas XYZ - Karay, Jeni; Manongga, Danny; Purnomo, Hindriyanto Dwi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
As a university, accreditation is a benchmark and recognition of quality standards and definitions of an educational institution (higher education) by parties outside an independent institution. Accreditation is also interpreted as an effort by the government to standardize and guarantee the quality of higher education alumni in order to ensure that quality among universities is not too varied and according to work needs. Management of Higher Education needs to improve quality and be an input for stakeholders who continue to improve the university. Using Soft System Methodology, researchers map and conceptualize models and plans to help XYZ University develop its accreditation values. In this case the Faculty of Science and Technology at XYZ University. From this research it was found that the XYZ University's Faculty of Science and Technology can provide alternative funding and development from all parties and grants as well as cooperation in outside universities that will help this faculty to add facilities, improve the quality of supervisors by using technology at the University's Faculty of Science and Technology XYZ. Recommendations given by researchers are faculties can make a web-based DSS (Decision Support System) accessed by intranet to help download traces of faculty development and can be used as a basis for decision making.